Kajian Faktor Dominan terhadap Penilaian Kinerja Sistem Penyediaan Air Minum (SPAM) di Provinsi Nusa Tenggara Barat : Study of Dominant Factors on Performance Assessment of Drinking Water Supply System (SPAM) in the Province of West Nusa Tenggara - Sudiarti, Sri Utami; Utama, Satria (Himpunan Ahli Teknik Hidraulik Indonesia (HATHI), 2024)
West Nusa Tenggara Province has 8 (eight) BUMDs (Regional Owned Enterprises) managing drinking water divided into two islands namely Lombok island and Sumbawa island where the study location is seven BUMDs. The two islands each have 4 (four) drinking water management bodies. There are four aspects of SPAM performance assessment based on PP 122/2015, namely financial aspects, service aspects, operational aspects, and human resource aspects. This study aims to find the dominant factors that influence the SPAM performance assessment. Quantitative research method applied using fuzzy cluster means (Fuzzy C-Means). The results showed that in the span of 2017 - 2022 the performance of SPAM Lombok island from 4 (four) BUMDs there are two healthy and two others less healthy. While Sumbawa island is less healthy on average. The dominant factors affecting the performance of these BUMDs are operational aspects and financial aspects where the dominant operational aspect is the level of water loss in the drinking water distribution system. The dominant financial aspect is liquidity including cash ratio and billing effectiveness. These dominant factors from the seven BUMDs obtained values that affect the BUMD performance value so that it falls into the category of healthy, less healthy and sick. This study results in efforts that need to be made to improve the performance condition of BUMD in the ‘sick’ category by knowing the dominant factors.